Maximal Efficiency of PSII as a Marker of Sorghum Development Fertilized With Waste From a Biomass Biodigestion to Methane - Romanowska-Duda, Zdzisława; Grzesik, Mieczysław; Janas, Regina (Frontiers in Plant Science, 2019)
The aim of experiments was to investigate a maximal efficiency of PSII, as a marker indicating growth, vigor, energetic value and physiological activity of sorghum fertilized with wastes from a biomass biodigestion to methane in a distillery integrated with a biogas plant using corn grains as substrate. The sorghum plants grown outdoor in different climate and in pots and in field were fertilized with different doses of the waste or Apol-humus – a soil improver and Stymjod – a nano-organic-mineral fertilizer. The maximal efficiency of PSII, in comparison with plant growth and health, chlorophyll content, gas exchange, activity of selected enzymes, element content in leaves and energetic value were studied. The wastes applied to soil resulted in increased maximal efficiency of PSII and the doses of 30 m3 ha-1 and 40–50 m3 ha-1 of the non-centrifuged and centrifuged ones, respectively, were most efficient. This enhancement was associated with the increased kinetics of plant growth, their health, fresh and dry biomass and physiological activity of plants as evidenced by activity of acid and alkaline phosphatase, RNase and dehydrogenase, as well as by gas exchange: net photosynthesis, transpiration, stomatal conductance, intercellular CO2 concentration and index of chlorophyll content in leaves. The fertilization with Apol-humus and Stymjod additionally increased maximal photochemical efficiency of PSII and plant development, biomass yield and physiological activity. The results indicate that waste from a biomass biodigestion to methane can be used as a natural fertilizer in sorghum crops and this ensures their recycling and environmental protection. The measurement values of maximal efficiency of PSII were proportionally to the vigor, growth and physiological activity of the plants. The obtained results indicate that the maximal efficiency of PSII in sorghum plants is a non-destructive method for defining the degree of growth and may be used as a marker of plant vigor and health, development and physiological activity expressed by gas exchange and activity of selected enzymes.